Effect of inoculums concentration, temperature and agitation rate on solvent production from palm oil mill effluent (POME) by Clostridium Beijerinckii ATCC 51743 - Fatimah Azzahra, Misebah (2012)
Few decades ago,world is totally depends on fossil fuel as energy source that currently most economically available source for personnel and commercial used leads in diminishing interest on development fermentation of biofuel industry.Unfortunately,due to constant conflict in the oil-supply regions and depletion of fuels oils supply resulted in viable of solventogenic fermentation industry in the world.Besides that,combustion of fossil fuel will produce various particle and gas that contribute to crises of environmental problem such as acid rain as well as greenhouse effect which is key factor in global warming. Thus,pressing need in reviewing the solventogenic fermentation of biofuel from a viable alternative sustainable and renewable energy resources that more renewable,more efficient and safer for environment. Unfortunately,the solventogenic fermentation needs to overcome high cost of production substrate together with low fermentation yield in order to compete with solvent production from fossil fuel.Palm oil mill effluent (POME) is abundant agricultural waste in Malaysia,shows great potential in used directly as alternative fermentation substrate.The objective of this study is manly to study the effect of temperature,agitation rate and inoculums concentration as variable factors that significantly influenced solvent production from palm oil mill effluent (POME) by Clostridium beijerinkii ATCC 51743.Analysis of total solvent production was done by using gas chromatography and isobutanol has been used as internal standard.Results that obtain from the study effect of 5 to 25% inoculums concentration to total solvent concentration show that the total solvent concentration will decrease as inoculums concentration increase.The highest production of total solvent is at 10% of inoculums concentration with 0.719 g/L production.Besides that,the study effect of 25 to 35 °C temperature to the total solvent production shows that concentration of total solvent production will decreases as temperature increase.The highest production is 0.568g/L at 30°C.Meanwhile effect of 50 to 250rpm agitation rate to the total solvent production shows that as agitation increases, total solvent production will decrease where the highest total solvent production was recorded at 150rpm with 0.675g/L.It can be conclude that,the temperature,agitation rate and concentration inoculums will be the significant parameter that affected production solvent from POME by Clostridium Beijerinckii (ATCC 51743).In addition, applying the Response Surface Methodology (RSM) was recommended for this study in order to determine the optimum level in enhances the solvent production.